A Porcine Epidemic Diarrhea Virus Outbreak in One Geographic Region of the United States: Descriptive Epidemiology and Investigation of the Possibility of Airborne Virus Spread. - Andrea Beam; Dane Goede; Andrew Fox; Mary Jane McCool; Goldlin Wall; Charles Haley; Robert Morrison (PLoS ONE)
This study describes a spring 2013 outbreak of porcine epidemic diarrhea virus (PEDv), using data from 222 swine sites in 14 counties area in 4 contiguous states in the United States. During the outbreak, the premises-level incidence of PEDv was 40.5 percent (90/222 sites). One of the three companies from which data were collected had a lower incidence (19.5 percent) than the other two companies (41.1 and 47.2 percent). Sow sites had the highest incidence of PEDv during the outbreak (80.0 percent). Spatial analysis showed that PEDv was clustered rather than randomly distributed, which suggested that sites near a positive site had increased risk of acquiring PEDv infection. Meteorological data were used to investigate the hypothesis that PEDv was spread by air. If airborne dissemination played a role in this outbreak, we would expect the direction of disease spread to correlate with the predominant wind direction. Two methods were used to determine the direction of disease spread--linear direction mean analysis in ArcGIS and the direction test in ClusterSeer. The former method indicated PEDv spread was south to slightly southwest, and the latter indicated spread was to the southeast. The predominant wind direction during the month of the outbreak was toward the south, with some southeast and southwest winds; the strongest wind gusts were toward the southwest. These findings support the hypothesis that PEDv was spread by air. The results, however, should be interpreted cautiously because we did not have information on direct and indirect contacts between sites, such as movement of trucks, feed, pigs or people. These types of contacts should be evaluated before pathogen spread is attributed to airborne mechanisms. Although this study did not provide a definitive assessment of airborne spread of PEDv, we believe the findings justify additional research to investigate this potential mechanism of transmission.